2016
DOI: 10.1155/2016/8485032
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Hemodynamics and Cognitive Function in Cirrhotic Patients with Hepatic Encephalopathy

Abstract: Aims. To investigate cerebral hemodynamics in cirrhotic patients with HE and to observe effects of treatment in cerebral hemodynamics and correlations among ammonia, cerebral hemodynamics, and cognitive function. Methods. There were four groups: healthy controls (group 1), cirrhosis without HE (group 2), cirrhosis with MHE (group 3), and cirrhosis with OHE (group 4). Ammonia and cerebral hemodynamics (by TCD) were assessed. Patients in group 3 were subsequently randomized to two subgroups: the control (group A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Patients with decompensated cirrhosis or HE have a higher risk of cerebral hypoperfusion related with microvascular damage and the ability for autoregulation, which is and important feature for systemic blood pressure sudden changes, particularly hypotension, which can promotes HE [84]. These findings were similar to those reported by two separated groups, one located in Turkey, were 50 decompensated group of cirrhotic patients was compared with 50 healthy volunteers using the same TCD approach [85]; while other in China recruited a healthy control group (n = 40), a cirrhotic without HE group (n = 52), a cirrhotic with MHE group (n = 21) and a cirrhotic with OHE group (n = 19) [86]. Here, in the first case, the authors analyzed the spectra signal derived from the systolic velocity, diastolic Astrocyte Pathophysiology in Liver Disease http://dx.doi.org/10.5772/intechopen.72506 velocity, mean flow velocity (MFV in cm/s), pulsatility, and the resistive indexes (PI = Peak sys-…”
Section: Clinical Data In Osmoregulation and Systemic Infections In Csupporting
confidence: 77%
See 1 more Smart Citation
“…Patients with decompensated cirrhosis or HE have a higher risk of cerebral hypoperfusion related with microvascular damage and the ability for autoregulation, which is and important feature for systemic blood pressure sudden changes, particularly hypotension, which can promotes HE [84]. These findings were similar to those reported by two separated groups, one located in Turkey, were 50 decompensated group of cirrhotic patients was compared with 50 healthy volunteers using the same TCD approach [85]; while other in China recruited a healthy control group (n = 40), a cirrhotic without HE group (n = 52), a cirrhotic with MHE group (n = 21) and a cirrhotic with OHE group (n = 19) [86]. Here, in the first case, the authors analyzed the spectra signal derived from the systolic velocity, diastolic Astrocyte Pathophysiology in Liver Disease http://dx.doi.org/10.5772/intechopen.72506 velocity, mean flow velocity (MFV in cm/s), pulsatility, and the resistive indexes (PI = Peak sys-…”
Section: Clinical Data In Osmoregulation and Systemic Infections In Csupporting
confidence: 77%
“…Patients with cirrhosis had a lower MFV compared to control healthy group, while cirrhotic patients had a higher PI and RI values and a positive correlation exists with the model for endstage liver disease (MELD) score and the RI values of patients with ascites, which were higher than those without ascites [85]. In the second case, authors found that mean velocity (V m ), V d , PI, and RI, as well as the serum ammonia levels, were decreased in the group of cirrhotic patients with MHE subject to lactulose treatment, when compared with the placebo group, while a positive correlation was found between ammonia and PI, RI, cognitive test results and V d ; authors propose that cerebral hemodynamics is related with the severity of HE and that lactulose treatment is able to significantly improve this parameter in cirrhotic patients [86].…”
Section: Clinical Data In Osmoregulation and Systemic Infections In Cmentioning
confidence: 89%
“…A subgroup analysis was undertaken according to Child–Pugh grade, which found that NCT‐A scores in the Child–Pugh A, B, and C groups were all significantly higher than that in the control group. As with ammonia levels, NCT‐A values showed an increasing trend with the decrease in liver compensatory ability; moreover, the worse the liver compensatory ability, the worse the cognitive ability of the patients, and the more prone they were to HE …”
Section: Discussionmentioning
confidence: 96%
“…In addition, the results of the present study may prompt a novel method to study other complications of cirrhosis, including portal hypertension (30), hepatic encephalopathy (31) and hepatocellular carcinoma (32,33). Table IV.…”
Section: Discussionmentioning
confidence: 82%